The Effect of Antenatal Corticosteroid Therapy to Respiratory Distress Syndrome Event on Preterm Infants in Surabaya - Devy Putri Zenita; Martono Tri Utomo; Ernawati Darmawan (Biomolecular and Health Science Journal, 2018)
ABSTARCTIntroductions: One of the most common cause of morbidity and mortality in premature infants is respiratory distress syndrome (RDS). Several studies have shown that a single dose administration of antenatal corticosteroid therapy in women who are at high risk for premature delivery was associated with decreased incidence of RDS. The study aims to determine the effect of antenatal corticosteroid therapy on the incidence of RDS in prematurity in the Department of Child Health Hospital Dr. Soetomo.Methods: Analytic observational case-control design study was used for this research. Samples were taken from the medical records of RDS patients in premature baby and non-RDS with 36 samples in each group.Results: Antenatal corticosteroid therapy has effect in RDS incidence (p = 0.016). While the results of the odds ratio was 0.298 (with 95% CI 0.110 to 0.810), it means that premature infants with antenatal corticosteroid therapy has 0.298 times lower risk than those who were not given antenatal corticosteroid therapy.Conclusion: Antenatal corticosteroid therapy did not provide a direct relathionship to the incidence of respiratory distress syndrome in premature infants, but it a protective factor that can reduce the incidence of RDS in prematurity.